The Effect of Transfer Pricing, Thin Capitalization, and Capital Intensity on Tax Agressiveness in Industrial Companies in Indonesia for the Period 2020-2024 - Suhartini, Suhartini; Parwati, Ni Made Suwitri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Tax aggressiveness is one of the strategies companies use to minimize their tax burden. This practice can lead to tax compliance issues and impact state revenue. This study aims to examine the influence of transfer pricing, thin capitalization, and capital intensity on tax aggressiveness in Indonesian industrial companies for the 2020-2024 period. Transfer pricing is assessed using related party transaction indicators, thin capitalization is assessed using the debt-to-equity ratio (DER), capital intensity is assessed using investment indicators in fixed assets, namely the capital intensity ratio (CIR), while tax aggressiveness is assessed from the effective tax rate (ETR). This study chose a quantitative approach from secondary data sources. The population in this study is divided into industrial companies recorded on the IDX for the 2020-2024 period, with a total population of 65 companies. The sampling technique was purposive sampling for a total sample of 12 companies from 60 observation data. Data analysis was carried out using the PLS-SEM (Partial Least Square) approach and processed using the WarpPls 8.0 application. The study findings indicate that Transfer Pricing and Thin Capitalization have a negative and significant impact on Tax Aggressiveness, while Capital Intensity has a positive and significant impact on Tax Aggressiveness.